Glucoseinsulin Mixture as a Cardioprotective Agent in Cardiology and Cardiac Surgery (Review) - I. A. Kozlov; T. V. Klypa (Общая реаниматология, 2017)
The literature review presents an analysis of publications describing the use of a glucose%insulin mixture as a cardioprotective agent in acute myocardial infarction and in cardiac surgeries with extracorporeal circulation (ECC). It summarizes historical aspects of implementation of the glucose%insulin therapy in cardiology and car%diac surgery. Possible mechanisms of action of the glucose-insulin-potassium mixture in acute ischemia and myocardial infarction were analyzed (normalization of electrical processes on the cardiomyocyte membrane, replenishment of metabolic substrates and increased production rate of adenosine triphosphoric acid due to glycolysis, decreased intensity of non%esterified fatty acid oxidation, decreased apoptosis, etc.). It discusses results of clinical studies evaluating prescription of the mixture for acute myocardial infarction, including data from metaanalyses. It demonstrated that the role and the clinical efficacy of the preventive and therapeutic measure under consideration in acute myocardial infarction are still the subject of discussion and require further research. It also analyzed modern concepts explaining the cardioprotective effects of insulin and glucose during surgeries with ECC (decreased insulin resistance, activation of anaplerosis, stimulation of intracellular signaling pathways maintaining the viability of cells, reduction of the severity of systemic inflammatory response, immunomodulatingeffect, etc.). Review discusses results of clinical studies including data from randomized clinical trials and metaanalyses performed over the last 5 years that demonstrated the absence of the effect of the glucose%insulin therapy on the hospital mortality. Various studies demonstrated its positive effects including decreased incidence of peri%operative myocardial infarctions and intensity of inotropic support, increased values of postoperative cardiac index, decreased duration of postoperative mechanical ventilation and ICU stay, etc. Review concludes that the interest to the therapeutic and preventive use of the glucose%-nsulin mixture in both emergency cardiology and cardiac surgery has been revived recently.